Action research to support teachers' classroom materials development. Issue 2 (3rd May 2016) - Edwards, Emily; Burns, Anne
ABSTRACT: Language teachers constantly create, adapt and evaluate classroom materials to develop new curricula and meet their learners' needs. It has long been argued (e.g. by Stenhouse, L. [1975]. An Introduction to Curriculum Research and Development. London: Heinemann) that teachers themselves, as opposed to managers or course book writers, are best placed to develop context-specific materials that effectively and affectively engage learners. However, a systematic approach is required for materials development, and one practical option is through action research. Action research enables teachers to investigate learners' reactions to new materials, and work with them to develop engaging context-specific materials. To illustrate how action research can successfully support materials development, this paper reports on a classroom-based project the first author (Emily) conducted at her college in Australia. The project was part of an innovative national programme for the Australian English Language Intensive Courses for Overseas Students (ELICOS) sector, initiated and facilitated by the second author (Anne) and the ELICOS peak body English Australia. An Assessment for Learning (AfL) theoretical framework was adopted to integrate lesson materials and assessment, based on learner needs. At the college, previous assessment preparation materials had been ad hoc, so Emily explored what materials would best support her learners in preparing for written assessments and feedback. Innovative classroom materials were developed in negotiation with learners, who were actively involved in the process through interviews, focus groups and surveys. Findings included improved AfL classroom materials and new self-study resources, as well as increased learner motivation. The paper concludes with analysis of the implications of using action research for materials development.